School assets and bullying in Chinese youth: A multiple mediation model of intentional self-regulation and internet gaming disorder - Xiong Gan; Ke-Nan Qin; Guo-Xing Xiang; Xin Jin; Cong-Shu Zhu (Frontiers Media S.A., 2022)
Bullying is a severe social problem affecting young people all over the world. Previous studies suggested that engagement in bullying had massive effects on teenagers' physical and psychological development. It is critical and necessary to investigate the antecedents and underlying mechanisms of this phenomenon among young generations. The present study, based on the positive youth development perspective and the developmental assets theory, attempts to explore the positive factors in the school subsystem that could effectively prevent adolescents from bullying, as well as the multiple mediation effects of intentional self-regulation (ISR) and internet gaming disorder (IGD). In this study, we adopted a two-wave design and recruited a sample of 768 Chinese adolescents using a randomized cluster sampling method in the post-pandemic era. The results revealed that T1 school assets significantly and negatively predicted T2 adolescent bullying. Furthermore, T2 ISR and T2 IGD mediated the association between T1 school assets and T2 bullying separately and sequentially. Overall, school resources play a protective role in adolescent development and could effectively prevent them from negative outcomes. These current findings contribute to the literature by providing a further understanding of the direct and indirect protective effects of school assets on adolescent bullying. Moreover, practitioners could also benefit from these findings in preventing and intervening in bullying in the school subsystem.